2021
DOI: 10.1525/elementa.2020.00062
|View full text |Cite
|
Sign up to set email alerts
|

Projecting ocean acidification impacts for the Gulf of Maine to 2050

Abstract: Ocean acidification (OA) is increasing predictably in the global ocean as rising levels of atmospheric carbon dioxide lead to higher oceanic concentrations of inorganic carbon. The Gulf of Maine (GOM) is a seasonally varying region of confluence for many processes that further affect the carbonate system including freshwater influences and high productivity, particularly near the coast where local processes impart a strong influence. Two main regions within the GOM currently experience carbonate conditions tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 113 publications
(170 reference statements)
1
26
0
2
Order By: Relevance
“…Wang et al (2017) observed a decrease of 0.01 in Ω aragonite for every 1 µmol/kg increase in dissolved inorganic carbon (DIC), similar to what has been observed in the open ocean (Bates et al, 2014). Recently, an oceanographic glider, an autonomous underwater vehicle, was used off the coast of New Jersey to measure subsurface pH levels, which ranged from 7.91 to 8.20, and to measure Ω aragonite , which ranged from 1.5 to 2.2 with higher readings at the surface (Saba et al, 2019).…”
Section: Fishery Bulletinsupporting
confidence: 52%
See 1 more Smart Citation
“…Wang et al (2017) observed a decrease of 0.01 in Ω aragonite for every 1 µmol/kg increase in dissolved inorganic carbon (DIC), similar to what has been observed in the open ocean (Bates et al, 2014). Recently, an oceanographic glider, an autonomous underwater vehicle, was used off the coast of New Jersey to measure subsurface pH levels, which ranged from 7.91 to 8.20, and to measure Ω aragonite , which ranged from 1.5 to 2.2 with higher readings at the surface (Saba et al, 2019).…”
Section: Fishery Bulletinsupporting
confidence: 52%
“…Movement of populations of Atlantic surfclam northward and into deeper water can be attributed to warming temperatures . Limited ρCO 2 data, combined with modeling results, indicate that decreases in pH and Ω aragonite occur in the areas to which Atlantic surfclam are moving (Wang, 2016;Saba et al, 2019;Friedland et al, 2020;Siedlecki et al, 2021). This study focused on only the ρCO 2 levels predicted for the RCP 6.0 and RCP 8.5 scenarios; we did not look at the role of increasing temperature.…”
Section: Discussionmentioning
confidence: 99%
“…We relied on an ensemble of high-resolution projections for ocean conditions in our region (Brickman et al, 2021). This article complements other Gulf of Maine 2050 scenario papers on ocean acidification (Siedlecki et al, 2021) and sea level rise and storms (Chisholm et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This rapid warming prompted the Gulf of Maine 2050 Symposium in November 2019. The Symposium asked participants to envision the future of the Gulf of Maine as it responds to three drivers of climate change: temperature and circulation, coastal and ocean acidification, and sealevel rise (Brickman et al, 2021;Chisholm et al, 2021;Siedlecki et al, 2021). For each of these drivers, current understanding of these drivers and how conditions are likely to change over the next 30 years were synthesized.…”
Section: Introductionmentioning
confidence: 99%